(untitled) (Studia austriaca, 2015)
Moving from the thesis that the question of happiness centers on ethics, this paper contributes to the clarification of the concept and then discusses happiness as it is represented in the works of Peter Handke. The peculiarity of these representations of happiness is that they thematize happiness anachronistically with regard to the relevant “Zeitgeist”. By tracing down the ways in which happiness is processed in Handke’s works and by comparing the social implications of these strategies, this paper satisfies the desideratum that arises from the fact that the ethics of happiness in the works of Peter Handke have hardly received any scholarly attention.